Meeting in the Oval Office with President Nixon - Lawrence Berkeley National Laboratory. Technical and Electronic Information Department (1969)
The White House Oval Office. L to R: Henry A. Kissinger, Robert F. Ellsworth, Patrick E. Haggerty (Chairman of Texas Instruments), President Richard M. Nixon, Glenn T. Seaborg, Lee A. DuBridge.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Nixon, Richard M. (Richard Milhous), 1913-1994; Nobel Prize winners